Journal of Research in Biology Effect of plant growth regulators on in vitro organogenesis in cultivated tomato (Solanum lycopersicum L - Nanna Rama Swamy (Journal of Research in Biology, 2011)
An efficient and reproducible protocol for organogenesis from cotyledon explants in cultivated tomato (Solanum lycopersicum L.) cv S-22 is reported. The cotyledon explants of 10-12 days old excised from in vitro grown seedlings were cultured on MS medium supplemented with 0.5-5.0 mg/L BAP as a sole growth regulator and also in combination with 0.1 mg/L IAA (Indole-3-acetic acid). Highest percentage of response for callus induction was recorded in cotyledon explants at 3.0 mg/L BAP where as multiple adventitious shoots were formed at 0.1 mg/L IAA + 2.5-5.0 mg/L BAP containing medium. Shoots obtained were transferred on to MS medium augmented with 0.2-1.0 mg/L GA3 + 3.5 mg/L BAP for shoot elongation. The medium supplemented with 0.6 mg/L GA3 in combination with 3.5 mg/L BAP showed the maximum percentage of enhancement of shoot elongation. For in vitro rooting, elongated micro-shoots were transferred onto MS medium supplemented with 0.5mg/L Indole-3-acetic acid (IAA) / Indole butyric acid (IBA) / Napthalene acetic acid (NAA). Profuse rhizogenesis was observed at 0.5 mg/L IAA compared to NAA / IBA. The regenerated plants were acclimatized in the culture room and maintained in the green house and transferred to the field. These plants were found to be normal and similar to the donar plant. Thus, an efficient and reproducible protocol has been developed in cultivated tomato cv S-22 which is genotype dependent. This protocol can be used for Agrobacterium tumefaciens mediated genetic transformation in tomato cv S-22